Biodiversity, seasonal abundance, and distribution of blackflies (Diptera: Simuliidae) in six different regions of Thailand - Wichai Srisuka (2018)
© 2017 The Author(s). Background: Blackflies are an important medical and veterinary group of small blood-sucking insects. Ninety-three blackfly species have been reported in Thailand. However, information on their biodiversity and population dynamics in each region is lacking. The main aim of this study was to assess the regional biodiversity, seasonal abundance and distribution of blackflies in six eco-geographically different regions in the country. Methods: Blackfly larvae and pupae were sampled monthly from 58 sites between May 2011 and April 2013. Diversity parameters, seasonal abundance, regional distribution and frequency of species occurrence in stream sites were analyzed. Results: A total of 19,456 mature larvae representing 57 species, and belonging to six subgenera in the genus Simulium Latreille (s.l.), were found. The five predominant taxa were S. fenestratum (8.6%), the S. asakoae complex (8.3%), S. nakhonense (7.5%), the S. siamense complex (7.4%) and the S. doipuiense complex (6.7%). The most frequent taxa at all sites were the S. asakoae complex (84.5%), followed by S. fenestratum (82.8%), the S. siamense complex (75.9%), S. decuplum (60.3%), S. nakhonense (58.6%) and the S. tani complex (48.3%). The richness of regional species was highest (40 species) in the north and predominated in the cold season. However, blackflies in the south predominated during the hot season. The highest numbers of blackflies collected from central, northeastern, eastern and western regions of the country were observed in the rainy season. Overall, the mean number of blackflies collected across the six regions during the rainy and cold season had no statistically significant difference, but it differed significantly in the hot season. Conclusions: Blackflies in Thailand were surveyed in all three seasons across six geographical regions. These findings demonstrated that blackfly communities at each stream site varied with seasonality, and the regional relative abundance of blackflies differed markedly in the hot season. It was also found that the occurrence and distribution of blackflies in each region were associated strongly with elevation.